A novel acrylic resin palatal device contaminated with Candida albicans biofilm for denture stomatitis induction in Wistar rats (Journal of Applied Oral Science, 2021)
Denture stomatitis is the most frequent oral lesion in removable prosthesis wearers, with high recurrence rates and a complex treatment. Objective: This study describes a protocol to obtain and to contaminate a palatal device with Candida albicans biofilm that could be used for an animal model of denture stomatitis. Methodology: Acrylic resin devices (N=41) were obtained from impressions of the palates of Wistar rats with individual trays and polyether. The efficacy of microwave irradiation (MW), ultraviolet light (UV), or ultrasonic bath (US) was assessed by colony viability and spectrophotometric analyses (n=5) in order to select the most appropriate method for sterilizing the devices. Then, different devices (n=5) were contaminated with C. albicans and evaluated by CFU/mL determination, scanning electron microscopy, and laser confocal microscopy. Device stabilization was assessed with either autopolymerizing acrylic resins or a self-adhesive resin cement (n=2). The spectrophotometric data were analyzed by one-way ANOVA followed by the Tukey’s HSD post-hoc test (α=0.05). Results: MW was the only method capable of sterilizing the devices, and the contamination protocol developed a mature and viable C. albicans biofilm (~1.2 x 106 CFU/mL). The self-adhesive resin cement was the best stabilization material. Conclusions: This acrylic resin palatal device was designed to be similar to the clinical situation of contaminated prostheses, with easy manufacturing and handling, effective stabilization, and satisfactory contamination. Thus, the acrylic device can be a valuable tool in the development of denture stomatitis in rats.